Combined application of two Bacillus species enhance phytoremediation potential of Brassica napus in an industrial metal-contaminated soil. Issue 6 (12th May 2022) - Jan, Sami Ullah; Rehman, Maha; Gul, Alvina; Fayyaz, Muhammad; Rehman, Shafiq Ur; Jamil, Muhammad
Abstract: This study aimed to assess the impact of individual as well as combined application of Lysinibacillus macroides and Bacillus safensis in phytoremediation potential of Brassica napus grown in soil contaminated by industrial effluents. In response to five metals; copper, chromium, nickel, lead, and cadmium, results revealed that germination percentage, fresh and dry weights, and photosynthetic pigments of B. napus decreased under contaminated soil. On the other hand, electrolyte leakage due to cellular injury, metabolites (proline and glycine betaine), antioxidant enzymes (superoxide dismutase, catalase, peroxidase, ascorbate peroxidase), accumulation of hydrogen peroxide and metals in plant's roots, shoots and leaves increased. Inoculation significantly reduced these effects as proved by the enhancement of germination percentage, fresh and dry biomass, and photosynthetic pigments. Simultaneously, the antioxidant enzymes, metabolites contents (proline and glycine betaine) and metal concentrations in plant's roots, shoots and leaves decreased. Combined application of both Bacilli strains was found more effective as compared to individual inoculation. It was concluded that metal resistant Bacillus species in combination had growth effects on B. napus and enhanced its phytoremediation efficiency in contaminated soil. Novelty statement Brassica napus ; a hyper-accumulator of metals, loses phytoremediation potential with the passage of growth. Two Bacillus species ( Lysinibacillus macroides and Bacillus safensis ) having known bioremediation abilities were employed individually as well as in combination under metals contaminated soil to increase phytoremediation efficiency of B. napus . The metals containing soil used is a unique aspect in this study because selected soil, contaminated by industrial effluents, has not been evaluated or reported earlier. Combined application of Bacilli improved phytoremediation potential of B. napus more as compared to application of individual Bacillus strain which is yet another unique aspect of this investigation.